Book review: Eric Williams: The myth and the man by Selwyn Ryan. Kingston: The University of the West Indies Press, 2009, pp. 842, ISBN: 978-976-640-207-5. - (:unkn) unknown (Department of History, The University of the West Indies, St. Augustine Campus,Trinidad and Tobago, 2011)
The review will draw attention to Selwyn Ryan’s extensive research on the topic and longstanding familiarity with the subject matter. It will comment on the strength, limitation and relevance of this recent work. Eric Williams was a noted Caribbean statesman and scholar. He served as Trinidad and Tobago’s first Premier and Prime Minister, and was that country’s Head of Government until his passing in 1981. As both a politician and an academic, Williams has done, stated and written much. Likewise, much has been said and written about Williams, regarding his contribution to global intellectualism, the development of Trinidad and Tobago and Caribbean civilization. There have also been a number of attempts to psycho-analyse Williams. This review proposes to locate this latest contribution by Selwyn Ryan in relation to the broad corpus of literature already devoted to the analysis of Eric William’s life and career. Additionally, it will explore Ryan’s approach to the challenge of delineating myth from fact regarding this important and outstanding Caribbean personality.

The publication information for the book being reviewed : Kingston: The University of the West Indies Press, 2009, pp. 842, ISBN: 978-976-640-207-5.
Keywords: Biographies -- Book reviews.; Statesmen -- Trinidad and Tobago -- Book reviews.; Politicians -- Trinidad and Tobago -- Book reviews.; Trinidad and Tobago -- Politics and government -- 1962.